Dose‐adjusted EPOCH‐R is not superior to sequential R‐CHOP/R‐ICE as a frontline treatment for newly diagnosed primary mediastinal B‐cell lymphoma: Results of a bi‐center retrospective study. (24th November 2021) - Morgenstern, Yael; Aumann, Shlomzion; Goldschmidt, Neta; Gatt, Moshe E.; Nachmias, Boaz; Horowitz, Netanel A.
Abstract: Purpose: Primary mediastinal B‐cell lymphoma (PMBCL) is a rare subtype of diffuse large B‐cell lymphoma (DLBCL). Despite its aggressive course, PMBCL is considered curable. While in recent years dose‐adjusted (DA) EPOCH‐R (rituximab, etoposide, prednisone, vincristine, cyclophosphamide and doxorubicin) has become widely endorsed as first‐line therapy for newly‐diagnosed PMBCL, the optimal treatment for this disease and the role of radiotherapy (RT) remains unclear. DA‐EPOCH‐R provides good clinical outcomes, albeit is associated with short‐ and long‐term toxicity. To address this issue, the current retrospective bi‐icenter analysis compared efficacy and toxicity of DA‐EPOCH‐R and a less toxic R‐CHOP/R‐ICE regimen used for the treatment of newly‐diagnosed PMBCL. Patients and Methods: The study included all patients with a histologically confirmed PMBCL diagnosis treated with DA‐EPOCH‐R or R‐CHOP/R‐ICE between 01/2013‐12/2020 at two tertiary medical centers. Patient demographic and clinical data were derived from institutional electronic medical records. The analysis included 56 patients: 31 received DA‐EPOCH‐R and 25 – R‐CHOP/R‐ICE. Results: At a median follow‐up of 1.9 years (IQR 3.1 years), similar progression‐free survival (2.1 versus 2.4 years; p = 0.7667), overall survival (2.5 versus 2.7 years; p = 0.8047) and complete response (80%) were observed in both groups. However, DA‐EPOCH‐R was associated with significantly longer hospitalization required for its administration ( p < 0.001) and a trend for higher frequency of infections, stomatitis, thrombotic complications and febrile neutropenia‐related hospitalizations. Conclusion: DA‐EPOCH‐R and R‐CHOP/R‐ICE provide similarly encouraging outcomes in newly‐diagnosed PMBCL patients. R‐CHOP/R‐ICE is associated with lower toxicity and significantly reduced hospitalization. Our findings suggest that this regimen may be considered as an alternative to DA‐EPOCH‐R in this patient population. Abstract : Primary mediastinal B‐cell lymphoma (PMBCL) is a rare subtype of diffuse large B‐cell lymphoma that is considered curable despite its aggressive course. DA‐EPOCH‐R, widely employed as a first‐line therapy for newly diagnosed PMBCL, offers good clinical results, but its utility is hampered by high rates of short‐ and long‐term toxicity. Our findings suggest that the use of R‐CHOP/R‐ICE could be consider as an alternative to DA‐EPOCH‐R in PMBCL patients, since the former regimen, while providing similarly encouraging outcomes, is associated with lower toxicity and significantly reduced hospitalization.